Way of an Indian - Remington, Frederic (Fox Duffield & Company New York, 1906)
"The Way of an Indian" is one of Remington's literary works, likely exploring themes related to the lives, cultures, and traditions of Native American tribes during the late 19th and early 20th centuries. The novel might offer insights into the customs, struggles, and ways of life of Indigenous peoples in the American West.
83811
Keywords: Southwest; Short Stories; Biographies; American Literature Anthologies